2014
DOI: 10.3899/jrheum.130902
|View full text |Cite
|
Sign up to set email alerts
|

Association of Bone Edema with the Progression of Bone Erosions Quantified by Hand Magnetic Resonance Imaging in Patients with Rheumatoid Arthritis in Remission

Abstract: Subclinical inflammation was identified by MRI in 96.4% of patients with RA in sustained clinical remission. Significantly higher scores of BME after sustained remission were observed in patients with progression of erosions compared to patients with no progression. The persistence of higher scores of BME may explain the progression of bone erosions in patients with persistent clinical remission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…when a joint is put under normal load from walking) has profound effects on cell behavior. A prime example of this in the clinic is bone marrow edema, where unnatural concentrations of stress on a person's bones cause cells (including hMSCs) to migrate away from the site of concentrated force, causing weakness and eventually erosion [59,60]). Alternatively, appropriate mechanical force can provide a strong environment for advantageous hMSC behavior and desirable differentiation.…”
Section: Enhanced Hmsc Functions On Electrospun Nano Scaffold With Camentioning
confidence: 99%
“…when a joint is put under normal load from walking) has profound effects on cell behavior. A prime example of this in the clinic is bone marrow edema, where unnatural concentrations of stress on a person's bones cause cells (including hMSCs) to migrate away from the site of concentrated force, causing weakness and eventually erosion [59,60]). Alternatively, appropriate mechanical force can provide a strong environment for advantageous hMSC behavior and desirable differentiation.…”
Section: Enhanced Hmsc Functions On Electrospun Nano Scaffold With Camentioning
confidence: 99%
“…These data suggest a link between BME and structural damage in RA. Indeed, the importance of BME is supported by several studies showing that BME is a predictor of radiographic evidence of progression [ 5 13 ]. A recent study even showed that the persisting presence of BME is associated with an odds ratio (OR) of 60 for erosive progression at the same location [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…On one hand, the lack of ultrasound activity predicts achievement and persistence of remission (33,34). On the other hand, there is a very high degree of confidence that residual synovial activity is a significant predictor for loss of remission (relapse, flare) and radiographic progression since controlled studies (35)(36)(37), meta-analyses (38,39), magnetic resonance imaging (MRI) studies (40)(41)(42)(43)(44)(45)(46), biological markers (14) and histology (47,48) have confirmed the cited ultrasound observations. The loss of remission tends to happen in the first year of follow-up (39), especially if treatment is withdrawn (49,50).…”
Section: Introductionmentioning
confidence: 72%